2007
DOI: 10.1007/s00330-006-0545-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dose reduction and feasibility of edge-preserving noise reduction on the detection of liver lesions using MSCT

Abstract: The purpose of this study was to assess the effect of dose reduction and the potential of noise reduction filters on image quality and the detection of liver lesions using MSCT. Twenty-nine patients with a total of 40 liver lesions underwent 16-slice CT (120 kV; 180 mAs). Virtual noise was added to CT raw datasets simulating effective mAs levels of 155, 130, 105, 80, 55, 30 and 10 mAs. All datasets were post-processed with an edge-preserving noise-reduction filter (ANR-3D), yielding a total of 15 datasets per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 16 publications
2
15
0
1
Order By: Relevance
“…The significant decrease in mean HU of the liver parenchyma from the early to late contrast phase was due to contrast washout. In general, our results are consistent with previously published phantom and patient studies, with non-linear 2D or 3D filters, on noise and radiation dose reduction for abdominal CT (5,7,8,14,16,19,20). For example, Rizzo et al Some recent CT radiation dose reduction studies using hybrid iterative reconstruction techniques have demonstrated up to 50-75% dose reduction for abdominal examinations (9).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The significant decrease in mean HU of the liver parenchyma from the early to late contrast phase was due to contrast washout. In general, our results are consistent with previously published phantom and patient studies, with non-linear 2D or 3D filters, on noise and radiation dose reduction for abdominal CT (5,7,8,14,16,19,20). For example, Rizzo et al Some recent CT radiation dose reduction studies using hybrid iterative reconstruction techniques have demonstrated up to 50-75% dose reduction for abdominal examinations (9).…”
Section: Discussionsupporting
confidence: 92%
“…Image postprocessing filters can operate in an image plane (2D filters) or within a volume including the z-direction (3D filters). Prior studies have evaluated the use of 2D (4-6) or 3D (7,8) filters, but to the best of our knowledge, no direct comparisons of 2D and 3D filters for enabling radiation dose reduction have been published at the time of preparation of this manuscript.…”
mentioning
confidence: 99%
“…Hence, the development of techniques for reducing the radiation dose becomes essential, because as the radiation increases, the associated risk of cancer also increases particularly in paediatric applications [5]. American College of Radiology have published guidelines to ensure that CT imaging protocols are optimized for the diagnostic image quality at the lowest radiation dose possible [6].…”
Section: Radiation Dose and Image Qualitymentioning
confidence: 99%
“…However, once the system's linearity comes into question, the MTF obtained from a high-CNR image can provide no information about the sharpness of low-CNR objects in clinical images. For example, ''nonlinear'' image filtering has become a common practice recently in CT, in order to suppress noise while maintaining or enhancing the sharpness of tissue edges [2][3][4]. Furthermore, whether linear or nonlinear, the blurring/enhancing effect of an image filter is dependent on the pixel pitch; the zoomed and filtered PSF image can never reflect the filtering effect on clinical images.…”
Section: Introductionmentioning
confidence: 98%